Mister Exam

Other calculators

Sum of series k^2-5*k+6



=

The solution

You have entered [src]
  oo                
 ___                
 \  `               
  \   / 2          \
  /   \k  - 5*k + 6/
 /__,               
n = 1               
n=1((k25k)+6)\sum_{n=1}^{\infty} \left(\left(k^{2} - 5 k\right) + 6\right)
Sum(k^2 - 5*k + 6, (n, 1, oo))
The radius of convergence of the power series
Given number:
(k25k)+6\left(k^{2} - 5 k\right) + 6
It is a series of species
an(cxx0)dna_{n} \left(c x - x_{0}\right)^{d n}
- power series.
The radius of convergence of a power series can be calculated by the formula:
Rd=x0+limnanan+1cR^{d} = \frac{x_{0} + \lim_{n \to \infty} \left|{\frac{a_{n}}{a_{n + 1}}}\right|}{c}
In this case
an=k25k+6a_{n} = k^{2} - 5 k + 6
and
x0=0x_{0} = 0
,
d=0d = 0
,
c=1c = 1
then
1=limn11 = \lim_{n \to \infty} 1
Let's take the limit
we find
True

False
The answer [src]
   /     2      \
oo*\6 + k  - 5*k/
(k25k+6)\infty \left(k^{2} - 5 k + 6\right)
oo*(6 + k^2 - 5*k)

    Examples of finding the sum of a series